Correlates of hepatitis b virus-related stigmatization experienced by Asians: A scoping review of literature - Haeok Lee; Jacqueline Fawcett; Deogwoon Kim; Jin Hyang Yang (Elsevier, 2016)
Objective: Although remarkable progress in the pharmacological components of the prevention and treatment of hepatitis B virus (HBV) and liver cancer has been achieved, HBV-related stigma is recognized as a major barrier to HBV management. The purpose of this Revised Social Network Model (rSNM)-guided review was to examine the existing research literature about HBV-related stigma among Asians and Asian immigrants residing in other countries. Methods: A scoping review of literature was conducted to determine the depth and breadth of literature. Totally, 21 publications were identified. The review findings were linked with the concepts of rSNM to demonstrate how individual factors and sociocultural contexts shape and affect the experience of HBV-related stigma. Results: Most studies were quantitative cross-sectional surveys or qualitative methods research that had been conducted among Chinese in China and in the USA. The three concepts in rSNM that have been identified as important to stigma experience are individual factors, sociocultural factors, and health behaviors. The major factors of most studies were on knowledge and attitudes toward HBV; only three studies focused on stigma as the primary purpose of the research. Few studies focused on the measurement of stigma, conceptual aspects of stigma, or interventions to alleviate the experience of being stigmatized. Conclusions: The scoping review revealed the existing depth and breadth of literature about HBV-related stigma. Gaps in the literature include lack of research address group-specific HBV-related stigma instruments and linkages between stigma and stigma-related factors.